Our land, our life, our future : black South African challenges to territorial segregation, 1913-1948 / Harvey Feinberg. - Feinberg, Harvey M. (Hidden histories series., 2015)
This ground-breaking book evaluates a topic central to the past century of South African history - the 1913 Natives Land Act and its consequences. Applying rigorous scholarly standards, Harvey Feinberg analyses, reassesses and then challenges previously accepted ideas about the impact of the Land Act. The book, a product of meticulous research in major South African archives, is notable for its reference to a wide array of documents scholars have until now neglected. A plethora of evidence provides the data to challenge major theories about the impact of the Natives Land Act, and to illuminate changes in government land policy. Objectively presenting this new evidence, Feinberg convincingly demonstrates that through African agency, black South Africans continued to buy land after 1913 thereby challenging the territorial segregation goals of the rural white population. His study also includes important contrasts between the 1910-1948 period and the apartheid era. This book will appeal to a wide readership, including international researchers interested in land history, South Africa-oriented academics, and the South African legal community - lawyers, policymakers and NGOs dealing with the land claims process. Readers interested in early 20th century South African history, and in the current debates over land policy and access to land, will be intrigued by this rich vein of new material, and will find that it includes important background information for the post-1994 restitution process.